Axillary surgery in breast cancer: An updated historical perspective - Magnoni, Francesca; Galimberti, Viviana; Corso, Giovanni; Intra, Mattia; Sacchini, Virgilio; Veronesi, Paolo (Seminars in oncology, 2020)
This historical surgical retrospection focuses on the temporal de-escalation axillary surgery, focusing on the unceasing efforts of researchers toward new challenges, as documented by extensive studies and trials. Axillary surgery has evolved, aiming to offer the best oncologic treatment and improve the quality of life of women. Axillary lymph-node dissection (ALND) has been replaced by sentinel lymph-node biopsy (SLNB) in women with early clinically node-negative breast cancer, providing adequate axillary nodal staging information with minimal morbidity, and becoming the standard of care in the management of breast cancer. However, this is only the beginning. Strategies in defining systemic and radiotherapeutic treatments have gradually been optimized, offering increasingly refined and targeted breast cancer treatment tools. In recent years, the paradigm of completion ALND after a positive SLNB has been questioned, and several studies have led to revolutionary changes in clinical practice. Moreover, the increasingly pivotal role played by neoadjuvant chemotherapy (NAC) has had a profound effect on the extent of axillary surgery, paving the way to a more finite "targeted" procedure in women with node-positive breast cancer who convert to negative nodes clinically after NAC. The utility of SLNB itself and its subsequent omission in women with negative nodes clinically and breast conservative surgery is also under scientific evaluation. The changes over time in the surgical approach to breast cancer have been numerous and significant. The novel emerging perspective characterized by recent advances in biology and genetics, in dedicated axillary ultrasound imaging and chemotherapy regimens, is the present reality that points to the future of axillary node treatment in breast cancer.